Implementasi E-Lkpd Interaktif Berbasis Kearifan Lokal Paghau Baganduang Untuk Meningkatkan Hasil Belajar Peserta Didik - Vista Cindy; Hendri Marhadi; Otang Kurniaman (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Interactive E-LKPD is an alternative media that can be used to support the learning process, consisting of materials and practice questions categorized as computer-based media because it requires a computer to operate, allowing students to independently enhance their understanding of the learning material.Interactive E-LKPD can make learning activities interactive, enjoyable, and have a positive impact on students' learning outcomes.This research aims to implement interactive E-LKPD that highlights the local wisdom of Paghau Baganduang in order to improve student learning outcomes in IPAS lessons for fourth-grade elementary school students.The research method used is an experimental method with a one group pretest-posttest design, conducted in the fourth grade of SDN 015 Pebaun Hilir.The data collection technique was conducted through pretests and posttests to determine the improvement in students' learning outcomes.The results of this study indicate an improvement in students' learning outcomes by 54.6%, with a pretest percentage of 26% and a posttest percentage of 80.6%.The N-gain score obtained was 0.74, categorized as "high."This study concludes that the use of E-LKPD based on local wisdom Paghau Baganduang can improve students' learning outcomes.